Assessment of Undergraduate Business Education Students' Usage of Social Networking as a Platform For Entrepreneurship Activities In North-West, Nigeria - Abubakar Mahmud; Adamu Ibrahim; Hamza Ismaila (Journal of Vocational Education Studies, 2021)
The study assessed the undergraduate business education students' usage of social networking as a platform for entrepreneurship activities in North-west, Nigeria. Specifically, the study had five objectives, five research questions and five null hypotheses. The study anchored theory of Technology Acceptance Model of Ajzen and Fishbein's, (1980) and Division of Innovation Theory (DOI) of Rogers (1995). The study adopted a survey research design. The population of this study comprises of all the 407 final undergraduate business education 2019/2020 academic session in North-west Nigeria. The entire population was used for the study. The instrument for the data collection was a structured questionnaire. The instrument was validated by four experts, pilot tested and a reliability coefficient of 0.81 was obtained. The data were collected by the researcher assisted by four research assistants using personal contact method. Descriptive statistics of mean and standard deviation was employed to answer the research questions. The hypotheses were tested using Analysis of Variance (ANOVA) at the 0.05 level of significance. The results revealed among others that the level of students' awareness, perceived ease of use and perceived usefulness of social networking as a platform for entrepreneurship activities in tertiary institutions in North-west Nigeria was low. Based on these, it was concluded that the business education will not reap the benefit of social networking sites to searcher for business opportunities, venture into business and meet the needs of their technologically savvy customers. It was recommended among others that business education lecturers should create awareness on students on the role of social networking as a platform for entrepreneurship activities.